Reimagining our space: Taking social justice principles online? - Avasha Rambiritch (University of Johannesburg, 2024)
Issues of social justice have been at the forefront in the quest to support students at the faculty-specific writing centre that is the focus of this study. This is in an effort to ensure that the centre remains not just a safe but a brave and non-judgemental space. The onset of Covid-19, and its imposition on our daily practices, required a hasty re-evaluation of our offering. This paper will outline our migration to a fully online mode of support and aims to establish whether the social justice principles harnessed in face-to-face support can and have been applied in the online platform. We approach this inquiry by evoking the voices of the writing centre consultants who spearhead our social justice agenda, with a view to determining their perceptions regarding this issue. Findings from such a study can be applied to the training offered to consultants in the hope of improving our offering.